IDEA OF THE ISLAMIC NATION IN ISLAMIC PHILOSOPHY - Majidov, R.H.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
Events based on nationalism in the Islamic world created great problems among Muslims. The conflict of nationalist ideas with Muslim teachings and a serious blow to the ideas of Muslim unity have led the Islamic world into an undesirable direction. It is known that the Islamic society was formed from a community of different nations, and this huge union united more than a billion people with a single idea, movement and feelings. The presence of elements of nationality in the minds of people who share the same beliefs and ideas of Islam caused some discomfort among Islamic reformers, and they formed a desire to replace national ideas with the concepts of an Islamic nation. When theoretical doctrines and philosophical concepts of nationalist ideas approached theology, disputes arose in many Islamic countries about national identity and nationality. This debate often took place in the context of a "special culture," and in all cases there were exaggerated discussions about Islamic culture. However, it should be noted that little is known about the strategy and concept of this culture, and the information provided is one-sided, and in some cases biased.